Are There Individual Differences in Social Interest During Visualization? - Heutmaker, Jessica (My University, 2010)
Individual differences in how people react to stressful situations, including the extent to which they want social interaction, are commonly found in the literature. We wondered whether, when they cope with having a terrible mood, (A) do extroverts differ from introverts and (B) do males differ from females in the extent to which they exhibit social interest. To explore these personality and gender differences, we administered an online survey to undergraduate participants as extroverted or introverted and participants indicated their sex.
Color poster with text and graphs.
Keywords: Personality--Social aspects; Adjustment (Psychology)--Psychological aspects; Adjustment (Psychology)--Sex differences; Social interaction--Psychological aspects; Social interaction--Sex differences; Stress management--Psychological aspects; Stress management--Sex differences; Posters